DEVIATIONS OF SPEECH ACTS IN BECKETT’S WAITING FOR GODOT: A STUDY IN PRAGMATICS - Mazhar Hayat; Saira Akhter; Sajida Iqbal (European Scientific Journal, ESJ, 2015)
Pragmatics interprets utterances in context, not in isolation and deals with all the sociological and psychological factors affecting the functioning of speech. The language of Waiting for Godot is conspicuous for deviations from the norms of formal conversation in context. A large number of utterances of the characters violate the principles of Speech Act Theory. The dialogues of the characters seem to convey nothing because of the hybrid utterances. The research paper aims to establish that these deviations from the normal speech patterns are instances of foregrounding which would yield a variety of meanings through Pragmatic study. Four extracts from the text of the play are selected for analysis under the theoretical framework of Austin and Searle’s Theory of Speech Acts keeping in view their stylistic and thematic significance.